Application of lithium nonafluoro-1-butane sulfonate (nonaflate) based non-aqueous liquid electrolytes (NALE) in lithium-ion batteries - Gurusamy,Hirankumar (2022)
ABSTRACT The non-aqueous electrolyte system comprising of the lithium nonafluoro-1-butane sulfonate (LiNfO) as a potential lithium ion-conducting salt in an equivalent binary mixture of propylene carbonate (PC) and 1, 2-dimethoxyethane (DME) as the solvent was explored for the lithium battery applications. The LiNfO based non-aqueous liquid electrolyte (NALE) system showed the highest ionic conductivity of 2.66 x 10-3 S cm-1 at ambient temperature, and a potential window stability of ~5 V. The lithium ion cells, Li/NALE//LiCoO2 were fabricated with the proposed non-aqueous electrolyte. The cell with particular composition of electrolyte delivered a high specific discharge capacity of 154 mA h g-1 at ambient temperature. The potential advantages of the proposed NALE are discussed in detail.